Percepción De Los Empleadores Acerca De Los Egresados Del Programa De Licenciatura En Educación Física Y Deportes De La Universidad Del Quindío (2014)
In this paper we will find the "perception of the employers about the graduates of the degree program in physical education and sports of the university Quindío". The research was based on the need to recognize employers' perceptions of the work performance of the graduates, seeking to improve, recognize and restructure a number of processes that improve and guide a firm path toward a secure goal that is Outlined in the program's mission. The development of this project took 11 months where a proposal was designed with a methodology of quantitative social approach of descriptive cross-sectional, the total population was taken with an institutional survey as instrument, which was designed and validated by the academic vice-rector and the group Of research and statistical consultancy, where the researcher proceeds to the analysis of information and the conclusion of results and the social impact of the extension projects, relationship between professional profile and performance, types of academic formation and of linkage to the institution or Company, relationship between performance and performance as the characteristics observed by the employer on the performance of graduates. Among the results were observed the relationship between the university, employers and the performance of the graduates such as their individual and group capacities.